Dr. B.R. Ambedkar’s Buddhism and Global Philosophies in the 21st Century - Nagaraja Chaluvadi Itigi; Anant Hanumanta Pujari; H.L. Patil, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Dr. B.R. Ambedkar’s interpretation of Buddhism represents one of the most profound intellectual and spiritual transformations in modern Indian history. His conversion to Buddhism in 1956, followed by the Navayana (New Vehicle) movement, redefined the religion as a philosophy of social equality, rationalism, and humanism. Ambedkar’s Buddhism transcended religious boundaries, linking ethics with social reform and emancipation from caste oppression. His reinterpretation of the Dhamma emphasized liberty, equality, and fraternity principles that resonate deeply with global philosophical traditions such as Western humanism, existentialism, and modern secular ethics. This paper analyzes Ambedkar’s Buddhist philosophy through the lens of global thought and explores its relevance in addressing 21st-century challenges such as social exclusion, environmental crisis, and moral alienation. Using secondary sources, it compares Ambedkar’s Buddhist ethics with global movements for peace, justice, and human dignity, situating him as a universal thinker whose ideas continue to influence scholars, reformers, and human rights movements across the world.
Keywords: Ambedkar; Buddhism; Navayana; Global Philosophy; Humanism; 21st Century